The Effectiveness of Using the Scramble Model in Reading Skills among Students at Al-Khair Association Junior High School Ciputat - Rahmi, Cindy Aulia; Muhbib Abdul Wahab; Fatimah El Zahra (Penerbit Minhaj Pustaka, 2026)
This study was conducted at MTs Jam’iyyaul Khair, Ciputat, South Tangerang, with the aim of determining the effectiveness of using the Scramble model in improving students’ reading comprehension skills. The study was motivated by a major problem, namely the low level of students’ ability to comprehend Arabic reading texts. Based on initial observations conducted by the researcher, it was found that many students still experienced difficulties in understanding the content of reading passages. To achieve the research objectives, an experimental method with a pretest–posttest control group design was employed. The research sample consisted of two classes: an experimental class taught using the Scramble model and a control class taught using conventional methods. The research instrument was a reading comprehension test, while data analysis employed the N-Gain test to measure the effectiveness of students’ reading comprehension and a t-test to determine the differences in mean scores between the two classes. The results showed that the experimental class achieved an N-Gain score of 0.50 (50.69%), which falls into the moderate category, while the control class obtained an N-Gain score of 0.22 (22.25%), categorized as low. The results of the t-test also indicated a statistically significant difference between the two classes. The researcher concluded that the Scramble model is more effective than conventional methods in improving students’ reading comprehension. Therefore, the Scramble model can be considered an alternative instructional strategy that teachers may use to enhance the quality of Arabic language learning, particularly in the area of reading comprehension. مستخلص البحث يهدف هذا البحث الذي قامت بها الباحثة في مدرسة